53 Transfer of care from hospital to home in the last days of life: is it safe and effective?. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hurlow, Adam; Laud, Rose; Patel, Arpit; Borrill, Deborah
Abstract : Background: Hospital teams must plan a safe and effective transfer of care for patients returning home in the last days of life. To support this Leeds Teaching Hospitals NHS Trust (LTHT) launched a revised Rapid Discharge Plan (RDP) in January 2014. Aim: To assess the quality of transfer of care (ToC) for patients returning home from LTHT who died within a week of discharge (June 2014 – May 2015). Methods: A convenience sample of 45 patients was selected from a database of 228. Clinical notes were reviewed for recognition of dying (prognosis days) pre-discharge, RDP use, and evidence of eight key interventions necessary for a successful ToC. Results: Median survival from discharge was 4 (1–7) days. Thirty-one (69%) had a progressive life-limiting illness and 12 (27%) had multi-morbidity/frailty. Twenty-five patients (56%) were recognised to be dying. Key interventions took place for the majority, including: advance care planning (ACP) (96%), Fast Track discharge (92%), anticipatory prescribing (88%) and do not attempt cardiopulmonary resuscitation form (DNACPR) (84%). The RDP was used in 11 (44%) of those recognised to be dying. The RDP patients had a median of six (5–8) key interventions compared to four (1–5) for those without an RDP. Eight (18%) were perceived to be in the last weeks to months of life and twelve (27%) were not recognised to be approaching the EoL at all. Ten (83%) of those not recognised to be near the EoL had multi-morbidity/frailty, whereas 29 (87%) of patients in the other two groups had a life-limiting illness. The majority (73%) of those not recognised had two or more markers of deteriorating health. Conclusion: Appropriate planning occurred for the majority of patients recognised to be dying. This was enhanced by use of the RDP. Recognition is a barrier to planning; particularly in those with multi-morbidity and frailty.